COVID-19 and rural livelihoods: Lessons from a longer-term assessment and the path to recovery - Berrospi, Maria Lucia; Ceballos, Francisco; Hernandez, Manuel A.; Paz, Cynthia (Elsevier, 2026)
The COVID-19 pandemic had profound effects on livelihoods across rural populations worldwide. Building on earlier work that examined the initial effects of the pandemic on food security and nutrition among smallholder agricultural households in the Western Highlands of Guatemala, this study offers a longer-term assessment of the impacts and the path to recovery. We rely on a unique longitudinal survey of 1,262 households conducted over four rounds between 2019 and 2022, with the first round in person and the subsequent ones by phone. The results show substantial recoveries in food security and dietary diversity in the region by mid-2022 compared to 2020, but at levels still worse than pre-pandemic ones for some indicators. There is also a sustained increase in the intention to emigrate. The households that were initially more affected in terms of food security and nutrition but recovered faster include those located in one of the three studied departments and families living above the poverty line, while smallholders affected by hurricanes, non-coffee producers, and indigenous populations took longer to recover. We additionally provide quantitative estimates for a subsample of households interviewed in person during a fifth survey round at the end of 2022, showing an average decline of about 16 percent in total household income three years after the start of the pandemic, mainly driven by a decrease in agricultural income, combined with a 26-percent increase in expenditures and an important surge in indebtedness. Overall, the study offers valuable lessons regarding the recovery of vulnerable households following a major global crisis and in a context of additional shocks.